AURICULOTEMPORAL NERVE AND FREY'S SYNDROME - Yanko Yankov (Peytchinski Publishing, 2023)
Background: The auriculotemporal nerve is one of the main branches of the mandibular nerve. It provides sensory innervation to the auricle, the scalp in the temporal region, the temporomandibular joint and part of the dura mater, the parasympathetic innervation of the parotid salivary gland, as well as the external surface of the tympanic membrane, and the sympathetic innervation of the sweat glands and of the blood vessels passing through the parotid gland. Its interruption during surgical interventions or trauma can results in its most common disease - Frey's syndrome. This article is an overview and is based on 23 foreign scientific works - articles published in refereed and renowned scientific publications and anatomy atlases by world-renowned and proven specialists in their field. Review Results: The auriculotemporal nerve is a sensory nerve which includes secretory parasympathetic vasomotor sympathetic fibers coming from the otic ganglion. It is a branch of the mandibular nerve (V3). Its five terminal nerve branches are front auricular branches, branches for the external auditory canal, branches for the temporomandibular joint, branches for the parotid gland and superficial temporal branches. Frey's syndrome occurs when the auriculotemporal nerve is cut or injured proximal to the site of separation of the branches for the parotid gland or are severed themselves. The clinical picture characteristic of Frey's syndrome includes redness, sweating, warmth and itching in the area of innervation of the nerve and less often pain. Conclusion: Knowledge of the anatomy of the auriculotemporal nerve and Frey's syndrome are essential for understanding its nature and stand on the basis of its prevention.